Novel magnetic properties of CoTe nanorods and diversified CoTe2 nanostructures obtained at different NaOH concentrations. Issue 1 (1st January 2017) - Lei, Yu-Xi; Miao, Nan-Xi; Zhou, Jian-Ping; Hassan, Qadeer Ul; Wang, Jing-Zhou
Abstract: CoTe and CoTe2 nanorods with average diameter of 100 nm were synthesized by a simple hydrothermal process, and different CoTe2 nanostructures were obtained by changing the NaOH concentration. CoTe nanorods exhibit weak ferromagnetism while CoTe2 nanorods present paramagnetic behavior. Different magnetic behaviors occur in the other CoTe2 nanostructures due to Na + entrance into CoTe2 crystals. A first-principles study on Na-doped CoTe2 confirms the magnetic characteristics. Abstract :